Assessing Knowledge, Attitudes, and Skills in Fixed Prosthodontic Procedures Among Dental Practitioners in Tripoli, Libya: A Cross-Sectional Study - Mohamed Altier,; Ahmed Mhanni,; Seham Elsawaay,; Majdi Seghayer, (AlQalam Journal of Medical and Applied Sciences, 2025)
Fixed partial dentures (FPDs) are a prevalent restorative option, yet their success hinges on adherence to standardized clinical protocols. This study aimed to evaluate the knowledge, attitudes, and practices (KAP) of dental practitioners (DPs) in Tripoli, Libya, regarding FPD procedures. A cross-sectional survey was conducted among 157 DPs in Tripoli, encompassing general practitioners (GPs), specialists, and those with varying clinical experience. A 21-item questionnaire assessed preoperative diagnostics, technical procedures, laboratory communication, and post-delivery care. Data were analyzed using descriptive statistics and chi-square tests. Clinical procedure differences were noted among gender, education, and experience. Females adhered more to preoperative radiographic procedures (p<0.001), while males managed implant prosthetics independently more often (p<0.012). Provisional crowns/bridges were more often performed by prosthodontists (p<0.005), and implant prosthetic independent management was more often performed (p<0.004). Practitioners with 1-3 years used common vitality testing (p<0.001), whereas those with more than 16 years utilized high-speed handpieces more (p<0.033). There were significant differences in impression disinfection (p<0.011) and interocclusal record materials (p<0.04) according to experience. Tooth preparation was unanimously considered the most important factor for FPD retention. This study highlights significant variations in FPD practices among DPs in Tripoli, indicating a need for targeted continuing education and standardization of clinical protocols to improve patient outcomes. المستخلص تعد الجسور الثابتة خيارًا شائعًا في ترميم الأسنان، إلا أن نجاحها يعتمد على الالتزام بالبروتوكولات السريرية القياسية. هدفت هذه الدراسة إلى تقييم مستوى المعرفة والمواقف والممارسات (لدى ممارسي طب الأسنان في طرابلس، ليبيا، فيما يتعلق بإجراءات الجسور الثابتة. تم إجراء دراسة مسحية مقطعية شملت 157 ممارسًا لطب الأسنان في طرابلس، من بينهم ممارسون عامون، وأخصائيون، وأطباء من ذوي الخبرات السريرية المتفاوتة. تضمن الاستبيان، المكون من 21 بندًا، تقييم التشخيصات قبل العلاج، والإجراءات التقنية، والتواصل مع المعامل، ورعاية ما بعد التركيب. تم تحليل البيانات باستخدام الإحصاءات الوصفية واختبارات مربع كاي. لوحظت فروق في الإجراءات السريرية بين الجنسين، ومستوى التعليم، والخبرة. أظهرت النتائج أن الإناث يلتزمن أكثر بإجراء الأشعة التشخيصية قبل العلاج (p<0.001)، في حين أن الذكور ينشؤون تعويضات السنية على الزرعات بشكل مستقل بمعدل أعلى (p<0.012) . كما تبين أن التيجان والجسور المؤقتة يتم تنفيذها بشكل أكبر من قبل أخصائيي تركيبات الأسنان (p<0.005)، وأنهم يقومون بصناعة التعويضات السنية على الزرعات بشكل مستقل في كثير من الأحيان (p<0.004). أظهر الممارسون ذوو الخبرة من 1-3 سنوات استخدامًا شائعًا لاختبار حيوية الأسنان (p<0.001)، بينما استخدم الممارسون الذين تزيد خبرتهم عن 16 عامًا إعداد الأسنان بأداة عالية السرعة (High speed handpiece) بمعدل أكبر (p<0.033) . كما لوحظت فروق كبيرة في تعقيم الطبعات السنية (p<0.011) ومواد تسجيل الإطباق(p<0.04) وفقًا لمستوى الخبرة. اتفق جميع المشاركين في الاستبيان على أن تحضير الأسنان هو العامل الأكثر أهمية في نجاح تثبيت الجسور الثابتة. تسلط هذه الدراسة الضوء على التباينات المهمة في ممارسة التركيبات الثابتة بين ممارسي طب الأسنان في طرابلس، مما يشير إلى الحاجة إلى برامج تعليم مستمر مستهدفة وتوحيد البروتوكولات السريرية لتحسين نتائج العلاج للمرضى